La reconstruction du lycée Le Verrier de Saint-Lô (Manche), 1944-1956 - Robert Blaizeau (In Situ)
The municipal collège of Saint-Lô (Manche Department), largely destroyed by the bombardments of the city in 1944, was rebuilt between 1948 and 1955 by Pierre Duprat (1919-2002) and Michel Pinget (1911-1987). Once the school became mixed in 1953 and converted into a “lycée” (France’s high school) in 1955, it took the name of the local astronomer, Urbain Le Verrier. Institutional and architectural developments were therefore combined during the post-war Reconstruction period in order to provide students with a modernised and comfortable school in compliance with the most recent requirements of the French Ministry of National Education.The case of Saint-Lô also illustrates the ambitions, the achievements and the limitations of the Second Reconstruction. The new “lycée” had to contribute to the renewal of Saint-Lô’s urban planning. In the end, it partially followed in the footsteps of the institution that already existed before the war (location, general layout inherited from the 19th century), for reasons mainly economic. But the contingencies on the construction site and the evolution of standards increased the costs and put a strain on the city finances for a long time. The institution was however deemed very successful, on the line of a unique decorative programme in the landscape of Saint-Lô, that combined sculptures and mosaics, such as a Planetarium (1957-1958) of Robert Couturier (1905-2008), now allocated to Saint-Lô Museum of Art and History.